Efficient total synthesis of calothrixin B - Bhosale, Shrikar M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient synthesis of calothrixin B (2) is demonstrated starting from 9H-carbazol-4-ol, having two one-pot reaction sequences as key steps. As a novel observation, DMF-methanol was shown to be a hydride donor for reduction of aldehyde to alcohol. Unexpectedly, nucleophilic substitution of benzyloxy by methoxy group was observed. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Calothrixin B; CAN; DMF-methanol; Hydride donor